Evaluation of cardiovascular disease program in Sleman District, Indonesia - Liena Sofiana; Rokhmayanti Rokhmayanti; Sulistyawati Sulistyawati; Desi Nurfita; Fardhiasih Dwi Astuti; Putri Arum Sholekhati (International Journal of Public Health Science (IJPHS), 2021)
Cardiovascular disease remains the biggest cause of death, while hypertension is the biggest risk factor for heart disease for 12 years from 2000 to 2012. Various programs to prevent and control hypertension have been carried out throughout the Sleman District Health Center, but the achievement of minimum service standards (SPM) hypertension has not met the target. The purpose of this study was to evaluate the cardiovasculer program in Sleman Regency, Indonesia. This research was mixed method design, with the sample consisted of 25 staff holding cardiovasculer program programs in health centers in Sleman Regency. The instruments used in this study were interview guides and check lists. Quantitative data analysis was conducted by entering data in spreadsheets and then categorizing, while qualitative analysis was conducted by using content analysis based on findings obtained from quantitative data. The results showed problems in the input aspect, namely the availability of human resources and facilities were still considered to be lacking, dual positions disturbed work effectiveness. In the aspect of the process it's good but there are still obstacles that are felt by the program holders. In the output aspect, Sleman Regency has not yet reached the SPM target for hypertension services.